PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE UNTUK MENINGKATKAN KETERAMPILAN PROSES PESERTA DIDIK PADA MUATAN IPAS KELAS V SDN 29/I TERUSAN - Asma’ul Husna; Faizal Chan; Issaura Sherly Pamela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was motivated by the lack of students‘ process skills which aims to describe the application of the Learning Cycle learning model to improve students’ process skills in the IPAS content in class V SDN 29/I Terusan. This research was conducted at SDN 29/I Terusan on 26 January 2024 to 26 February 2024. The research approach used classroom action research which was carried out in two cycles in which each cycle had two meetings and there were four stages, namely planning, implementation, observation, and reflection. The research instruments used observation, tests and documentation. The results showed that the learning cycle learning model can improve the process skills of students in the content of IPAS V SDN 29/I Terusan. The increase can be seen from the data analysis of each cycle. cycle I meeting 1 reached 49.45% then at meeting II to 56.33%. Cycle II meeting I reached 61.77% at meeting II to 75.00%. Based on the results of the research that has been carried out, it can be concluded that the application of the learning cycle learning model can improve the skills of fifth grade students in the IPAS content. This can be seen from the increase in the process skills of students on the content of IPAS reaching ≥70